PELAKSANAAN PEMBUATAN DAN PENGIRIMAN LAPORAN DATA KEADAAN MORBIDITAS DAN MORTALITAS PASIEN RAWAT INAP (RL4a) DI RSJ GRHASIA DIY - , OKTRINA DIAN PRATIWI, Nur Rokhman, S.Si., M.Kom. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: According Peraturan Menteri Kesehatan Republik Indonesia Nomor 1171/MENKES/PER/VI/2011 each hospital must implement the Hospital Information System (SIRS). SIRS is an application hospital reporting system that consists of the process of collecting, processing and presenting hospital data to the Ministry of Health which include hospital identity data, the data workforce who work in hospital, recapitulation service activities data, compilation disease/ inpatients morbidity data, and compilation disease/ outpatients morbidity data. Purpose: to knowing implementation production and the obstacle encountered in the producing inpatients morbidity and mortality state data reports in RSJ Grhasia DIY, to knowing the suitability out date patients between HIS and medical record file, to knowing implementation of delivery inpatients morbidity and mortality state data reports in RSJ Grhasia DIY to Sleman District Health Office, Health Department of DIY Government and DG of Medical Care. Methods: This research used a descriptive qualitative approach with phenomenology research design. The data collection techniques are used observation, interviews and documentation studies. Subject in this research are indexing officer, reporting officer, and Head of Medical Record Instalation in RSJ Grhasia DIY. Object in this research are the inpatients medical record file which back to the medical record installation, out patients data in HIS and state data reporting inpatients morbidity and mortality. Results: Input state data reporting inpatients morbidity and mortality include medical record file and HIS, process which include indexing, entry out patients data, and inpatients morbidity and mortality report recapitulation, and output include state data reporting inpatients morbidity and mortality (RL4a). The obstacle such as delay in returned the medical record file, HIS has not maximum in operation, and computer reporting damaged due to lightning. Percentage of suitability out date between HIS and Medical Record File in February was 90,84% and 9,16 % mismatch. Shipment state data reporting inpatients morbidity and mortality in RSJ Grhasia to Sleman District Health Office, Health Department of DIY Government done by sending via email while the DG of Medical Care is done by uploading a file to an official website of Ministry of Health Director General BUK RI.